Sudden Cardiac Death and Its Prevention Ways among Athletes According to Iranian Traditional Medicine. - Marzieh-Baygom Siahpoosh; Mohammad Ebadiani; Gholamreza Shah Hosseini; Haleh Dadgostar; Mohammad Mahdi Isfahani; Alireza Nikbakht Nasrabadi (Iranian Journal of Public Health, 2013)
In the modern medical era sudden cardiac death and its causes among athletes have been described. Finding appropriate preventive ways from this tragic event is so important in sports medicine. According to different trials and observations, there are numerous reasons and some preventive strategies. Historically, sudden cardiac death among athletes had been described several hundred years ago by ancient physicians. The first physician who described this topic completely and recommended some preventive ways is Ibn Abi Sadiq al-Neishaburi. In this article, his opinion has been discussed.